My Union, My Life: Jean-Claude Parrot and the Canadian Union of Postal Workers - Parrot, Jean-Claude (Fernwood, 2005)
Jean-Claude Parrot was National President of the Canadian Union of Postal Workers for fifteen years and its chief negotiator for eighteen. During that time he provided the leadership which built what became Canada’s most militant and democratic union. When Pierre Trudeau decided to make the post office a crown corporation Parrot was there to guide the transition. He was also there to oversee the merger of the various postal unions into “one union for all.” As well as Jean-Claude Parrot’s story, this is also the story of the formation of a union. It is a story of how union democracy was built–of how the grassroots union membership became an integral part of decision making in the union. In the pages of this book you will follow the life of one of Canada’s greatest union leaders as he fought to give the workers a voice. In the course of the struggle Parrot often put his union work and commitments before his own personal life and spent time in prison rather than sacrifice his principles and the cause of the workers in the union. Through Parrot’s recounting of these years we learn about how the struggle was waged, how democracy was built and how a union leadership worked tirelessly in the service of the union membership. –Publisher's description
https://fernwoodpublishing.ca/book/my-union-my-life
Keywords: Biography; Canadian Union of Postal Workers; Officials and employees; Parrot; Jean-Claude; Postal service